2015
DOI: 10.1080/15299716.2014.984372
|View full text |Cite
|
Sign up to set email alerts
|

Identities and Identifications: Changes in Metropolitan Bisexual Men's Attitudes and Experiences

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
0
22
1
Order By: Relevance
“…This differs from some of the past qualitative research which has suggested that identity issues are a major reason for non-disclosure among bisexual men (Baldwin et al, in press; McCormack et al, 2015; McLean, 2007; Wheeler, 2006). However, this difference may be attributable to some of this past research being largely focused on understanding issues of bisexual identity, rather than on reasons for non-disclosure.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…This differs from some of the past qualitative research which has suggested that identity issues are a major reason for non-disclosure among bisexual men (Baldwin et al, in press; McCormack et al, 2015; McLean, 2007; Wheeler, 2006). However, this difference may be attributable to some of this past research being largely focused on understanding issues of bisexual identity, rather than on reasons for non-disclosure.…”
Section: Discussioncontrasting
confidence: 83%
“…However, other reasons for non-disclosure depart from those anticipated by stigma management theory. For example, consistent with the identity development perspective, some men have reported not disclosing because they do not identify as bisexual or are uncertain about their sexual identity (Baldwin et al, in press, McCormack, Wignall, & Anderson, 2015; Wheeler, 2006). Other studies have found that some behaviorally-bisexual men report they conceal their sexual orientation because they feel others have no right to know this personal information, even their female sexual partners if they consistently use condoms (Malebranche et al, 2010; Schrimshaw et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some youth described using the bisexual category as the best option to describe their sexual attractions and behaviors accounting for incongruence they were experiencing. Prior work has found similar occurrences among young men (McCormack et al, 2015). Others described being less defined by their sexuality, but all described interpersonal pressure to conform to commonly held belief in dichotomous sexuality (e.g., gay or straight) and traditional masculine role expectations (e.g., produce children with a wife).…”
Section: Discussionmentioning
confidence: 55%
“…This ranges from a “post-identity phase” where categories do not resonate with youth, to needing a bisexual category as the best option to describe their sexual desires without stating one’s own affiliation (McCormack, Wignall, & Anderson, 2015). Others have suggested that Latino and Black gay-identified youth describe awareness of same-sex attractions through fantasies, “crushes,” emotional attachments or arousal toward other males (Jamil et al, 2009).…”
Section: Introductionmentioning
confidence: 99%